2014
DOI: 10.1097/iop.0b013e3182a74f21
|View full text |Cite
|
Sign up to set email alerts
|

Eyelid Margin Basal Cell Carcinoma Managed With Full-Thickness En-Face Frozen Section Histopathology

Abstract: Eyelid margin BCC can be managed effectively with full-thickness en-face frozen section-controlled excision and primary reconstruction of the defect. The high cure rate compares favorably with other excision techniques such as Mohs micrographic surgery, with the advantages of a single operation and excellent reconstructive result.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Eyelid margin SGC was excised with full-thickness en-face frozen section-controlled technique as described by Gill et al 12. The main lesion was excised, followed by excision of 1 mm full-thickness medial, lateral and inferior/superior margins to make up for a 5 mm margin.…”
Section: Methodsmentioning
confidence: 99%
“…Eyelid margin SGC was excised with full-thickness en-face frozen section-controlled technique as described by Gill et al 12. The main lesion was excised, followed by excision of 1 mm full-thickness medial, lateral and inferior/superior margins to make up for a 5 mm margin.…”
Section: Methodsmentioning
confidence: 99%
“…Recurrence rates after frozen section controlled excision were reported as 1.7% by Gayre et al, 13 4% by Nemet et al, 10 0.7% by Wong et al, 24 0.26% by Ho et al 25 and 1.3% by Gill et al, 26 while no recurrence was observed by Conway et al 27 after 5 years, by Taherian et al 28 after 38 months or by Akbaş Kocaoğlu et al 29 in Turkey after 18.7 months of follow-up.…”
Section: Discussionmentioning
confidence: 98%
“…The long-term benefits of Mohs surgery compared with other techniques is still unknown [26]. Full-thickness en-face frozen section has also been shown to be effective with comparable results to Mohs surgery for basal cell carcinoma [27,28]. In a recent report from MD Anderson Cancer Center, using complete surgical excision of SC with en-face margin evaluation on frozen section, the local recurrence rate was only 6% [9].…”
Section: Discussionmentioning
confidence: 99%